Relationships of exercise regimen and racetrack surface to modeling/remodeling of the third metacarpal bone in two year-old Thoroughbred racehorses - Nunamaker, D. M. (Veterinary and Comparative Orthopaedics and Traumatology, 2002)
The effects of two different training regimens, two different racetrack surfaces (dirt and woodchip), as well as no training (control) were studied to determine their relationships to bone modeling/remodeling and cross-sectional inertial properties in the third metacarpal bone (Mclll) of the young Thoroughbred racehorse. Eight two-year old Thoroughbred racehorses were divided into four groups and subjected to different training regimens over a period of five months. At the end of the training period 100 micron cross sections of Mclll were examined using microradiography and the cross-sectional inertial properties of MCI 11 were determined. The results showed striking differences in the appearance of the bone cross sections with most of the bone modeling occurring on the dorso- medial surface of the ‘classically’ exercised animals and bone deposition on the dorsal surface in the ‘Modified-Classical’ training groups. Inertial properties were different between the groups with the ‘Classically’ trained animals having Imin values similar to the control group while the ‘Modified-Classically’ trained group had large increases in Imin at the mid diaphysis similar to reported measurements of older racehorses. These areal measurements of the cross sections, indicating resistance to bending in the dorsal palmar direction, showed the effects of training on the individual groups.
Keywords: Bone inertial properties; bucked shins; bone fatigue; bone modeling; bone remodeling